The Roles of E-Service Quality, E-Trust, and E-Satisfaction on Online Retail Loyalty - Dewi Purnamasari (Prosiding Industrial Research Workshop and National Seminar, 2018)
The concept of customer loyalty is complex and difficult to define, as it encompasses a number of interactionswith other variables. In addition, creating customer loyalty in the online business setting is more problematic thanin the offline business. Several studies have examined a number of antecedent variables of customer loyalty, buthow online retail business makes their customer stay loyal is not much understood. The objectives of this studyare to identify the roles of service quality, customer trust and customer satisfaction on customer loyalty in anonline retail setting. Using 480 online retail customers in Bandung as respondents, this study reveals that all ofthe antecedent variables on customer loyalty have positive and significant relationships toward customer loyaltyin retail online. In addition, there is a positive and significant interrelationship between customer satisfaction andcustomer trust. However, service quality has the largest effect on customer trust, and customer trust has a highervalue than customer satisfaction as mediation variable between service quality and customer loyalty. The findingsof this study are of benefit for online retail business in determining the best strategy to achieve customer loyalty.